1992
DOI: 10.1002/j.1460-2075.1992.tb05219.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and functional expression of the Na/Ca,K-exchanger from bovine rod photoreceptors.

Abstract: Complementary DNA encoding the Na/Ca,K‐exchanger was isolated from bovine retina cDNA libraries. The complete full‐length cDNA is approximately 4 kb long and contains an open reading frame of 3597 bp. The deduced amino acid sequence corresponds to a protein of 1199 amino acids with a calculated molecular weight of approximately 130 kDa. Hydrophobicity analysis revealed the presence of two alternating sets of hydrophobic and hydrophilic domains. There also exists a hydrophobic region at the N‐terminus which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 45 publications
(31 reference statements)
3
121
1
Order By: Relevance
“…Comparison of the deduced amino acid sequence of this novel gene (Figs. 1 and 2) revealed a significant level of similarity to the two known members of the K ϩ -dependent Na ϩ /Ca 2ϩ exchanger family as follows: NCKX1, first identified in retinal rod outer segments (19), and NCKX2, originally identified in rat brain and then in chicken and human retinal cone and ganglion cells (28,29). Thus, the novel gene presented here encodes the third member of the K ϩ -dependent Na ϩ /Ca 2ϩ exchanger gene family and will be referred to as NCKX3 (gene SLC24A3).…”
Section: Identification In Human Brain and Skeletal Muscle Of A Novelmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the deduced amino acid sequence of this novel gene (Figs. 1 and 2) revealed a significant level of similarity to the two known members of the K ϩ -dependent Na ϩ /Ca 2ϩ exchanger family as follows: NCKX1, first identified in retinal rod outer segments (19), and NCKX2, originally identified in rat brain and then in chicken and human retinal cone and ganglion cells (28,29). Thus, the novel gene presented here encodes the third member of the K ϩ -dependent Na ϩ /Ca 2ϩ exchanger gene family and will be referred to as NCKX3 (gene SLC24A3).…”
Section: Identification In Human Brain and Skeletal Muscle Of A Novelmentioning
confidence: 99%
“…NCKX1 was first cloned from bovine retina (19) and, more recently, from other species including dolphin, rat, buffalo, and man (20 -22). This protein 1 The abbreviations used are: NCX, Na ϩ /Ca 2ϩ exchanger; EST, expressed sequence tags; kb, kilobase pair; MOPS, 3-(N-morpholino)propane-sulfonic acid; NCKX, Na ϩ /Ca 2ϩ ϩ K ϩ exchanger; PCR, polymerase chain reaction; RT-PCR, reverse transcription-coupled polymerase chain reaction.…”
mentioning
confidence: 99%
“…NCX1 is predominantly expressed in the heart, brain, and kidney, although it is also present in a broad variety of cell types, whereas NCX2 and 3 expression is limited to brain and skeletal muscle (38,42,43). NCKX1 is exclusively expressed in retinal rod outer segments, whereas NCKX2 is expressed in brain and cone photoreceptors (47,48,59). NCKX3 and 4 display a broader pattern of tissue expression, although they are also prominently expressed in the brain (31,36,39).…”
Section: K + -Dependent and Independent Na + /Ca 2+ Exchangersmentioning
confidence: 99%
“…The first K + -dependent Na + /Ca 2+ exchanger to be identified by molecular cloning was NCKX1 from bovine rod photoreceptors (48). Northern blotting and in situ hybridization have demonstrated that the mRNA encoding for this exchanger is found almost exclusively in rod photoreceptors (39).…”
Section: Localizationmentioning
confidence: 99%
“…Cloning of bovine RodX (bRodX) 1 was reported by Reilaender et al (2), and the authors suggested that, similar to the cardiac exchanger, the N terminus may function as a cleaved signal sequence. If, in fact, the first 65 aa constitute a cleaved signal sequence, the large N-terminal hydrophilic domain would not be anchored to the membrane by a preceding transmembrane segment.…”
mentioning
confidence: 98%